Designing for Local, communicating for Global: Bilingual Typography and the Symbol of the new logo for the Cyprus University of Technology - Zantides, Evripides (My University, 2020)
The Cyprus University of Technology was founded on December 2003 and welcomed its first students on September 2007. Since its establishment, the University has been using for its logo an icon of a fifth century Byzantine mosaic known as the goddess Ktisis (KTICIC), a personification symbolising the creation of the world. The specific image is exposed for public viewing at the ancient theatre of Curium in Limassol-Cyprus, and is arbitrarily photographed by a number of local companies and institutions as a symbol of their logo and brand strategy as well. Because of issues of copyrights and accessibility, in addition to serious problems of readability and adaptation in various applications, mediums, and sizes, the senate decided to proceed with a refinement, as well as ask for the option to design a new logo for the Cyprus University of Technology. That would differentiate it from the rest and diminish its current typographic and graphic design problems. Additionally, the whole idea would contribute to the re-branding actions that the University decided to proceed in 2017. The aim of the current paper is to present the design process that was undertaken for the development of a new logotype, and show the conceptualisation of its various typographic and design stages. Particularly, the presentation will build on the reasons that lead to a visual identity change, discuss current trends and aesthetics of University logos, analyse the typographic, design and semiotic parameters that should be considered when redefining logotypes, as well as argue the benefits of a new visual identity and long-term branding. In addition, the presentation will explore how the name of the University is typographically adjusted to support its bilingual adaptation in both languages, for its local audiences in Greek and for its international in English.
Keywords: Typography